Digital competence of secondary school teachers in Mérida, Yucatán (Innovaciones Educativas, 2023)
Currently, it is essential that teachers at the basic level acquire and develop digital competencies in order to adapt to the needs and demands of a digitized society, in order to support students to face the challenges of an increasingly globalized world. For the above-mentioned, this paper aims to analyze the self-perception of teachers at a secondary school in Merida, Yucatan, regarding their digital competence. The research is based on a quantitative approach, with a correlational study design, with transectional, observational and retrospective temporality. Descriptive statistics were used to show the level of digital competence of the teachers and chi-squared tests and analysis of variance to determine their relationship with the variables: gender, age, degree of education and area of knowledge. Among the results, we can highlight that of the 6 dimensions that make up the digital teaching competence (DTC), in 5 of them the teachers showed a low level; concerning the relationships of the dimensions of the DTC with the variables gender, degree of education and area of knowledge, no significant difference was found; on the other hand, with the variable age, there was a significant difference regarding the dimensions of communication, collaboration and information, and with information literacy.
Keywords: Information technology; Basic education; Digital Competence; Digital skills; Secondary school teacher